Music in the Labyrinths of Clio: Historiographical Reflections on Chilean Production (Revista Argentina de Musicología, 2018)
On the basis of his experience in teaching and research, the author reflects on some aspects of the relationships music-history and time-music, focusing specifically on the production of Chilean historiography. He observes the lack of important updated accounts examining possible reasons among which he highlights the “specter of the short term”, and the trends towards memory building and the revival of relatively recent periods. This implies that the music investigator may gradually become an expert in problems and cases rather than periods and processes. He also deplores the lack of a sound co-account in historical accounts about music before the twentieth century.
Keywords: Historiography; Chilean Music; Time and Music